The Effect of Tax Planning and Current Tax Expense on Earnings Management Before and After Income Tax Rate Changes - Rengganis, Dita; Soetardjo, Mulyadi Noto (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2023)
The objectives of this study are to investigate whether tax planning and current tax expense have an impact on firm’s earnings management practices and to investigate whether such impacts are different in the periods of before and after income tax rate changes. This study uses OLS to regress Tax Retention Rate and Current Tax Expense toward Discretionary Accruals and to regress the interaction of main independent variables and Tax Rate Change toward Discretionary Accruals. The number of samples used in this study were 203 samples for 5 years taken from S&P Capital IQ database using the purposive sampling method. The results of this study indicate that both tax planning and current tax expense do not have a significant effect on earnings management practices. Also, the changes in income tax rates do not affect the influence of tax planning on earnings management and current tax expense on earnings management. This study shows that in the selected sample the earnings management practices are not affected by all taxation aspects in the firms.